The effectiveness of decision-making training in team-sport officials: A systematic review and meta-analysis - Kittel, A.; Lindsay, R.; Larkin, P.; Spittle, M.; Cunningham, I. (Psychology of Sport and Exercise, 2025)
Purpose Decision making is a critical skill for sports officials, often directly influencing the flow and fairness of a match. While this topic has received considerable interest in the literature, a synthesis of current evidence to understand the effectiveness of decision-making training interventions remains unexplored. Therefore, the aim of this study was to conduct a systematic review and meta-analysis of decision-making interventions in team sport officials.